A single-cross, RNA interference-based genetic tool for examining the long-term maintenance of homeostatic plasticity - Brusich, Douglas J.; Spring, Ashlyn M.; Frank, C. Andrew (Frontiers in Cellular Neuroscience, 2015)
Homeostatic synaptic plasticity (HSP) helps neurons and synapses maintain physiologically appropriate levels of output. The fruit fly Drosophila melanogaster larval neuromuscular junction (NMJ) is a valuable model for studying HSP. Here we introduce a genetic tool that allows fruit fly researchers to examine the lifelong maintenance of HSP with a single cross. The tool is a fruit fly stock that combines the GAL4/UAS expression system with RNA interference (RNAi)-based knock down of a glutamate receptor subunit gene. With this stock, we uncover important new information about the maintenance of HSP. We address an open question about the role that presynaptic CaV2-type Ca2+ channels play in NMJ homeostasis. Published experiments have demonstrated that hypomorphic missense mutations in the CaV2 α1a subunit gene cacophony (cac) can impair homeostatic plasticity at the NMJ. Here we report that reducing cac expression levels by RNAi is not sufficient to impair homeostatic plasticity. The presence of wild-type channels appears to support HSP – even when total CaV2 function is severely reduced. We also conduct an RNAi- and electrophysiology-based screen to identify new factors required for sustained homeostatic signaling throughout development. We uncover novel roles in HSP for Drosophila homologs of Cysteine string protein (CSP) and Phospholipase Cβ (Plc21C). We characterize those roles through follow-up genetic tests. We discuss how CSP, Plc21C, and associated factors could modulate presynaptic CaV2 function, presynaptic Ca2+ handling, or other signaling processes crucial for sustained homeostatic regulation of NMJ function throughout development. Our findings expand the scope of signaling pathways and processes that contribute to the durable strength of the NMJ.